New cooking oil from virgin coconut-palm olein blends - Omar, Muhammad Nor; Mohd Roslee, Farhani; Zuberdi, Ahmad Muzammil; Mohd Daud, Jamaluddin (2011)
The effects of virgin coconut oil in palm olein during deep-fat frying of French fries for 8 hours per day for five consecutive days were compared in this study. Nowadays, the reusing of oil is normal procedure but it gave a major impact to human health. Thus, this study was done to improve the oil stability during frying by blending. The oils that were used in this study were of control oil (100% palm olein (PO)), VCO/PO (10:90 v/v), and VCO/PO (20:80 v/v). All samples of frying oils were periodically collected, and their free fatty acid (FFA) content, total polar content (TPC) and total polymer material (TPM) were examined. The results of this study indicated that virgin coconut oil (VCO) can be used to improve oil stability in palm olein during deep frying. The oils became darker, increased in yellow color at the beginning, and became yellow-reddish throughout the process. For all physicochemical properties studied, the blends of VCO and palm olein oil during frying process were better than palm olein only. VCO/PO (20:80 v/v) showed the lowest total polar content while VCO/PO (10:90 v/v) was lowest in total polymer material. In terms of FFA, the decreasing order of the percentage of FFA was: VCO/PO (10:90 v/v) > VCO/PO (20:80 v/v) > control oil. Therefore, this study suggests that a blend of palm olein and VCO showed a slight improvement in frying performance over control oil. For sensory evaluation, it showed that there was no significant difference in oiliness while there was a significant difference (*p < 0.05) in colour, odour, crispiness, taste and overall score and acceptability of French fries fried in all three different oil samples. In general, frying stability of the palm olein was improved by the blending of small proportions of virgin coconut oil into the palm olein.